Between exploitation and exploration of motor behaviours: unpacking the constraints-led approach to foster nonlinear learning in physical education. (4th March 2019) - Komar, John; Potdevin, François; Chollet, Didier; Seifert, Ludovic
ABSTRACT: Introduction : The constraints-led approach (CLA) and more generally a complex systems perspective on motor learning emphasizes the role of perceptual-motor exploration during learning in order to ensure the acquisition of a highly individualized, adapted and adaptable movement pattern. Recent studies have shown that human beings have a strong tendency to exploit already stable patterns rather than looking for new potentially more efficient patterns. In order to shape the amount of exploration, we implemented two learning designs based on a CLA where constraints were used to limit the boundaries of the perceptual-motor workspace of the learners. We sought to highlight how practitioners can play with the perceptual motor workspace boundaries in order to (i) promote the use of exploratory behaviours and (ii) guide the learner towards task-relevant functional areas. Method : For the experiment, twenty-four beginners in breaststroke swimming were allocated to three groups of learning: a control group receiving only the goal of the learning, an analogy group receiving the goal of learning accompanied by an analogy about 'how to perform', a pacer group receiving information on the goal of learning and the use of a metronome to continuously push them to 'perform better'. Based on their assigned group, each learner then followed a learning protocol of 16 sessions with a 10*25 m swimming distance per session with the goal of increasing the stroke length for a fixed swimming speed. Both performance (i.e. stroke length) and motor behaviour (i.e. arm-leg coordination) were collected for each session. The arm-leg coordination patterns were computed by the continuous relative phase between knee and elbow angles. Thereafter, a cluster analysis was performed on the coordination in order to get a qualitative label for every cycle performed during the entire process of learning. Based on the use of cluster analysis, an exploration/exploitation ratio was calculated and the increase in performance was determined based on the increase in stroke length. Results and Discussion : With reference to the exploration/exploitation ratio, our results showed that additional temporary constraints-led learners to increase both the nature of their exploration and also the quantity of their exploration. In the meantime, the three groups showed an equivalent final performance enhancement. The aim of manipulating the constraints was not only to push the learner out of his comfort zone, but also to provide relevant information about 'where' to explore during learning. For this purpose, the use of analogy appeared as the most relevant constraint to encourage the emergence of efficient behaviour. Interestingly the impact of the analogy was modified by adding the metronome, showing an interaction effect of both constraints. The group using the metronome exhibited different behaviours as compared to the analogy group and showed an increase in exploration during learning compared to the control group. However, although the metronome constantly pushed the learner to improve performance, it did not actually lead to a better improvement of performance when compared to the analogy group. The simple assumption that the constraints forced the learner to explore therefore does not seem a mandatory condition to promote an exploratory learning. Rather, the qualitative nature of the constraint seems the most relevant characteristic that can be manipulated to promote an exploratory learning by guiding the learner within the perceptual motor workspace.